Participant profiling analysis for the kelulutpreneurs incubator under the community engagement project of UiTM Cawangan Melaka and Yayasan TM / Zunaidah Ab Hasan … [et al.] - Ab Hasan, Zunaidah; Othman, Azhana; Che Man, Norajila; Rabu, Noormala; Mohd Adnan, Sarah Dina; Mohd Aziz, Mohd Khairul Nizam (2023)
This research paper presents a participant profiling analysis conducted for the Kelulutpreneurs Incubator; an integral component of the Community Engagement Project initiated by Universiti Teknologi MARA (UiTM) Cawangan Melaka in collaboration with Yayasan TM. The project aims to empower and uplift local beekeeping entrepreneurs, known as Kelulutpreneurs, through specialized incubation programs tailored to their needs. The primary objective of this study was to comprehensively profile the aspiring and existing Kelulutpreneurs participating in the incubator program. The profiling process encompassed socio-demographic data, entrepreneurial experience, educational background, motivations, challenges, and aspirations. By understanding the unique characteristics and attributes of these Kelulutpreneurs, the incubator can tailor its programs and support services to cater to their specific requirements effectively. Utilizing a mixed-methods approach, both qualitative and quantitative data were collected from the participants through surveys and interviews. The qualitative analysis provided rich insights into the participants' personal experiences and perceptions, while the quantitative data enabled the identification of key trends and patterns. The findings revealed a diverse group of Kelulutpreneurs, ranging from enthusiastic newcomers with limited experience to seasoned entrepreneurs seeking innovation and growth opportunities. The results of this participant profiling analysis provide valuable inputs to enhance the Kelulutpreneurs Incubator's impact and effectiveness. The tailored support services and training programs can be optimized to address the specific needs and aspirations of the Kelulutpreneurs, thereby fostering their growth and sustainability. Furthermore, this research contributes to the body of knowledge on community engagement initiatives and their potential for empowering local entrepreneurs to drive positive change in their communities.